Identifying M.A and PhD Students' Point of View Regarding Effective Factors in Establishing Communication between Students and Faculty Members of School of Allied Health at Tehran University of Medical Sciences in 2012- 2013 Academic Year - javad ghazi mir saeed; Abolfazl Taheri; MohammadMoradi joo (Zanjan University of Medical Sciences and Health Services, 2017)
Background and Objective: One of the most important factors in education process is establishing communication between students and their professors. Effective education except scientific skills, needs using effective communication methods in educational environments. This can be done by recognizing effective factors in establishing communication. Therefore, the purpose of this study was to identify M.A and PhD students' point of view regarding effective factors in establishing communication between students and faculty members. Materials and Methods: In this descriptive- cross sectional study, M.A and PhD students of Allied Health Faculty of Tehran University of Medical Sciences were surveyed. Data gathering tool consisted of two parts; demographic data and 28 questions related to the assessment of effective factors in establishing communication between students and faculty members. The questionnaire was a four point scale ranging from "very effective" to "having no effect". Data was analyzed by SPSS 18.ed software, using descriptive statistical methods, frequency distribution, determining percentage and the group comparison was made by chi2. Results: The most effective factors according to students' viewpoint were, respect for students (86.3%), being up to date (78.4%), rhetoric and teaching skills (71%) and secrecy (71%) in establishing communication between students and their professors. Meanwhile, sex, age gap, stringency and professors' appearance were not so crucial in establishing communication. Conclusion: The result of this study showed that personal factors like rhetoric and teaching skills, behavioral characteristics such as respecting students in comparison with other factors like scientific skills and professional features are more effective in establishing communication.